Long-Term Outcome of Kidney Transplantation for IgA Nephropathy: A Single-Center Experiences. (July 2018) - Tadokoro, Akira; Tasaki, Masayuki; Saito, Kazuhide; Nakagawa, Yuki; Ikeda, Masahiro; Imai, Naofumi; Ito, Yumi; Takahashi, Kota; Tomita, Yoshihiko
Abstract : Background: Immunoglobulin A nephropathy (IgAN) is the most common primary glomerulonephritis worldwide, with a high recurrence rate after kidney transplantation (KTx). The aim of this study was to assess allograft survival, impact of recurrence on allograft function, and risk factors for post-transplant IgAN recurrence. Methods: A total of 443 patients received KTx between March 1998 and August 2017 in Niigata University in Japan. We identified 104 patients with primary IgAN who underwent KTx and diagnosed recurrence of IgAN in 26 patients by graft biopsies. Graft biopsies were performed when urinary tests showed abnormal after KTx. Recurrence rate of IgAN, graft survival, the risk factors of recurrent IgAN and the results of treatment for recurrent IgAN were investigated. Results: Median duration of follow-up was 119.5 months (1-259). Graft survival was not significantly different between the patients with primary IgAN compared with those with other primary diseases. IgAN recurrence rate at 1, 5, 10, and 20 years after KTx was 2 %, 16.5 %, 30.2 %, and 42.4 %, respectively. When graft survival was compared between the patients with IgAN recurrence and non-IgAN recurrence in the patients with primary IgAN, they were not significantly different (87.8 % vs 88.4 % at 10 years after KTx, respectively). The older age more than 30 y.o at KTx, the use of mycophenorate mofetil and basiliximab were associated with a lower risk of IgAN recurrence. Twenty patients underwent tonsillectomy and 24 patients received steroid pulse therapy (19 patients received both therapies). One patient didn't receive any treatment for IgAN recurrence. Median follow-up period was 51 months (2-175) after treatment for IgAN recurrence. The improvement of mesangial IgA deposition showed in 6 out of 15 patients who underwent graft biopsy after treatment. Five patients (19.2 % in recurrent IgAN patients) lost their graft function due to IgAN recurrence during follow-up periods. Conclusions: Recurrent IgAN remains a significant cause of graft loss in transplant recipients. Recipients with recurrent IgAN after KTx, especially younger patients, need to be followed up carefully.